Dynamic assessment on high school biology students’ reasoning skills - Murni Ramli; Mayasari Mahfudhotul Khasanah; Sri Dwiastuti (Biosfer: Jurnal Pendidikan Biologi, 2021)
Reasoning skills of students may be improved through a sort of feedback constructed in the dynamic assessment. The research aims to analyze the effect of dynamic assessment on high school biology students' reasoning skills. The research employs a quasi-experimental method with a pretest-posttest control group design. The participants were students of grade X Science Program (N=61), which were selected purposively. Data on reasoning skills was collected by pretest and posttest focused on the concepts of bacteria. with dynamic assessment method. The data analysis technique employs an Independent sample t-test. The research result indicate that Dynamic Assessment provides better effect on students’ reasoning skills in Bacteria material.